Traditional Sasi wisdom in Papua-based nature conservation. (February 2019) - Sumarsono, A; Wasa, C
Abstract: The existence of forests in Papua in some areas which are already inhabited has been conserved by a local and traditional ways, one of them is Sasi . This research revealed one of the positive impacts of the Sasi . The research used ethnic pedagogical approach. The qualitative data were obtained from observation, interview and focus group discussion. On the hand, quantitative data were obtained from questionnaires. The results show that the native Papuans in Merauke district (Onggaya, Tomer, and Kuler) have understood the description of Sasi . 84% of the respondents understood the history of Sasi, usability, and abstinence if violating the Sasi . Types of existing Sasi consist of the custom Sasi, the church Sasi, and the village Sasi . The Sasi was existed in plants, fish pond (swamp), water. The residents of three villages agreed that the sustainability of Sasi would be continued until posterity. The purpose of Sasi is to share welfare of using the results as well as preserving the natural environment of Papua. Naturally, Sasi can be used as a traditional natural conservation media.